Alpha-1 antitrypsin mitigates the inhibition of airway epithelial cell repair by neutrophil elastase - Garratt, L.W.; Sutanto, E.N.; Ling, K.M.; Looi, K.; Iosifidis, T.; Martinovich, K.M.; Shaw, N.C.; Buckley, A.G.; Kicic-Starcevich, E.; Lannigan, F.J.; Knight, D.A.; Stick, S.M.; et al. (AMER THORACIC SOC, 2016)
Copyright © 2016 by the American Thoracic Society. Neutrophil elastase (NE) activity is associated with many destructive lung diseases and is a predictor for structural lung damage in early cystic fibrosis (CF), which suggests normal maintenance of airway epitheliumis prevented byuninhibitedNE.However, limited data exist on how the NE activity in airways of very young children with CF affects function of the epithelia. The aimof this studywas to determine if NE activity could inhibit epithelial homeostasis and repair and whether any functional effect was reversible by antiprotease alpha-1 antitrypsin (a1AT) treatment. Viability, inflammation, apoptosis, and proliferation were assessed in healthy non-CF and CF pediatric primary airway epithelial cells (pAEC non-CF and pAEC CF , respectively) during exposure to physiologically relevant NE. The effect of NE activity on pAEC CF wound repair was also assessed.We report that viability after 48 hours was significantly decreased by 100 nM NE in pAEC non-CF and pAEC CF owing to rapid cellular detachment that was accompanied by inflammatory cytokine release. Furthermore, both phenotypes initiated an apoptotic response to 100 nM NE, whereas ≥50 nM NE activity significantly inhibited the proliferative capacity of cultures. Similar concentrations of NE also significantly inhibited wound repair of pAEC CF , but this effect was reversed by the addition of a1AT. Collectively, our results demonstrate free NE activity is deleterious for epithelial homeostasis and support the hypothesis that proteases inthe airway contribute directly toCF structural lung disease. Our results also highlight the need to investigate antiprotease therapies in early CF disease in more detail.